Recent progress on elucidating the molecular mechanism of plasmid-mediated colistin resistance and drug design - Kai, Jindan (Int Microbiol, 2019)
Antibiotic resistance is a growing global challenge to public health. Polymyxin is considered to be the last-resort antibiotic against most gram-negative bacteria. Recently, discoveries of a plasmid-mediated, transferable mobilized polymyxin resistance gene (mcr-1) in many countries have heralded the increased threat of the imminent emergence of pan-drug-resistant super bacteria. MCR-1 is an inner membrane protein that enables bacteria to develop resistance to polymyxin by transferring phosphoethanolamine to lipid A. However, the mechanism associated with polymyxin resistance has yet to be elucidated, and few drugs exist to address this issue. Here, we review our current understanding regarding MCR-1 and small molecule inhibitors to provide a detailed enzymatic mechanism of MCR-1 and the associated implications for drug design. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10123-019-00112-1) contains supplementary material, which is available to authorized users.